2020
DOI: 10.3390/w12020444
|View full text |Cite
|
Sign up to set email alerts
|

Cotransport of Cu with Graphene Oxide in Saturated Porous Media with Varying Degrees of Geochemical Heterogeneity

Abstract: Graphene oxide (GO) is likely to encounter heavy metals due to its widespread use and inevitable release into the subsurface environment, where the ubiquitous presence of iron oxides (e.g., hematite) would affect their interaction and transport. The present study aimed to investigate the cotransport of GO (20 mg L−1) and copper (0.05 mM CuCl2) in the presence of varying degrees of geochemical heterogeneity represented by iron oxide-coated sand fractions (ω = 0‒0.45) in water-saturated columns under environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Moreover, as reported in the study, the colloids have the potential to promote the transport of heavy metals in soils and groundwater [19]. In recent years, the co-transport of colloids and contaminants has attracted widespread attention regarding environmental remediation due to its prevalence and efficient treatment in groundwater [20][21][22]. It was reported that colloids are well dispersed, which can provide highly potential adsorption material for heavy metal removal [23,24].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, as reported in the study, the colloids have the potential to promote the transport of heavy metals in soils and groundwater [19]. In recent years, the co-transport of colloids and contaminants has attracted widespread attention regarding environmental remediation due to its prevalence and efficient treatment in groundwater [20][21][22]. It was reported that colloids are well dispersed, which can provide highly potential adsorption material for heavy metal removal [23,24].…”
Section: Introductionmentioning
confidence: 79%
“…The effect of colloids on contaminant transport is dependent on hydrogeological conditions and physicochemical properties of the aquifers [27][28][29][30]. Both groundwater chemistry and site-specific conditions may promote or hinder the co-transport of heavy metals and natural colloids in the subsurface environment [20,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of HA, the BTCs demonstrate a delayed breakthrough of Al2O3NPs (Figure 6c). The NOM yields a negative surface charge and electrosteric stability to the Al2O3 NPs due to the binding of carboxylic (COOH) and phenolic functional groups (R-OH) to the surface of particle, which enhanced the Al2O3 transit along column (Davoudi et al 2014;He et al 2020;Rahman et al 2014). Also, the presence of HA increased the stability of the suspension and inhibits aggregation via improving electrostatic repulsion and steric hindrance as shown in the sedimentation experiments (Figure 6d).…”
Section: Effect Of the Environmental Parameters On Column Transportmentioning
confidence: 94%
“…1,2 The rapid increase in the use of this carbon-based nanomaterial will inevitably lead to the release of GO into environmental systems (e.g., soil, surface water, and aquifers). 1,3,4 Recent studies have conrmed that harmful effects on natural ecosystems and living organisms have occurred aer exposure to GO. [5][6][7][8] Understanding the transport, deposition, and fate of GO colloidal particles in subsurface formations is of great importance for numerous applications, regulatory approaches, and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%